Report of propose new interior design of Nintendo Centre for Gamers Hideout Sdn Bhd at Lot UG 046,001-002, Plaza Low Yat Shopping Complex, Bukit Bintang, Kuala Lumpur / Abdul Hannan Abd Nashir - Abd Nashir, Abdul Hannan (Faculty of Architecture, Planning and Surveying, 2010)
The finale of Diploma in Interior Design is a project which will be the manifesto to a final year student, it is all about what the student learn and be taught about along three years studying in Interior Design will be practise in the final project. The chosen project is Nintendo Centre for Gamers hiedout sdn bhd at Lot UG 046,001-002, Plaza Low Yat Shopping Complex, Bukit Bintang, Kuala Lumpur. The porpose gaming centre that specifically for Nintendo lover’s is to design a gathering place for fellow gamers, apart from being a specialty store for Nintendo. The target customer is mainly teenagers, apart from youngsters and adult without gender constrains. Concept and images chosen are competitive and suits the image of the product. Therefore would reflect the image of th e client itself. Attractive proposal should be done to attract more customer and gain more popularity among it competitor. Futuristic with retro elements is differents from the other and should fulfill the end user’s requirements. Before choosing the image and concept, building and site analysis has been done so that every potential of the site can be manipulated. The propose area in the centre and all the inventory should be listed and study carefully so that it wont create any trouble in the design process. The info gained about the project, the images are gain from the vast amount of media today, with the internet, printed media and though the case study either locally or internationally.